Two Sides of the Same Pill? Fertility Control and Mental Health Effects of the Contraceptive Pill - Franziska Valder (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
I investigate the link between access to the contraceptive pill, mental health, and labor market outcomes. While liberalizing labor market effects of access to the pill are well established, a medical literature suggests a link between hormonal contraception and depression. Exploiting variation in access to the pill, I document substantial mental health effects of the pill. These mental health effects counteract the fertility control effect of the pill on labor market outcomes and are associated with limitations at work and more disability periods. The analysis also shows that the fertility control effect of the pill is larger than previously estimated.
Keywords: J16; J13; J18; J24; I0; 330; Mental Health; Contraceptive Pill; Fertility; Labor Market Outcomes